Analysis of the most common stressful factors for emergency care nurses - Gerasimova, Lolita; Mikaliūkštienė, Aldona (Slauga. Mokslas ir praktika, 2023)
The work of emergency nurses involves long working hours, providing assistance in the event of life-threatening conditions, accidents, trauma patients, and anxious family members of patients. These are all stressful factors at work. Intensive and stressful work can have an impact on their physical and emotional health over time. The aim of the study is to select and analyse scientific articles on key stressors in the work of emergency care nurses. The research method is a literature review. The search for scientific publications was carried out using the PubMed search engine in the electronic database. Used keywords in English: stress at work, emergency nurses, the causes of stress. violence, bullying. The selected 31 articles are written in English. The results showed that emergency care workers face a range of situations every day, some of which can be life-threatening and require emergency care and intensive care. This dynamic environment, which also affects factors such as violence and bullying, stressful situations and high workload, puts emergency care workers under severe stress at work.